Medium-short chain fatty acids cannot spare the essential fatty acids of low marine diets in golden pompano (Trachinotus ovatus) - Huang, Xingcan; Chen, Fang; Sang, Yuhang; Li, Yuanyou; Xie, Dizhi (Aquaculture reports, 2024)
Based on the essential fatty acids (EFA) precision nutrition, a blend oil (BO) of fish oil and terrestrial oils was developed, and applied successfully to the low marine diets of golden pompano (Trachinotus ovatus). To evaluate whether medium- and short-chain fatty acids (MCFA and SCFA), efficient energy supplements for animals, can spare the dietary EFA, four iso-proteic (48%) and iso-lipidic (11%) low fishmeal (FM) diets (D1-D4, contained 6% FM) were formulated and fed T. ovatus juveniles (initial weight ∼8.50 g) for 9 weeks in sea cages. Control diets (D1) contained 8% BO, while the BO of diets D2-D4 were replaced 50% with coconut oil, coconut oil + sodium butyrate, and coconut oil + n-3 LC-PUFA enriched oil, respectively. The results showed that compared to the D1 group, the growth performance of D2 and D3 were significantly lower, while a comparable growth was detected in the D4 group. The muscle and hepatic n-3 PUFA levels in the D2 and D3 groups were significantly low, and these fatty acid contents were modified in the D4 group. Meanwhile, the muscle textural firmness of the D2-D4 groups was decreased. Regarding the health index of fish, compared to the D1 group, high serum triglyceride (TG) contents and low HDL/LDL ratio were detected in the D2-D4 groups, and high ACP, AST, and ALT activities were observed in these groups. Meanwhile, high HSI and low hepatic enzymatic activities of CAT and ALT were measured in the D2-D3 groups. Additionally, the mRNA levels of hepatic fatty acid synthesis-related genes (fas, acc, and pparγ) were significantly increased in D2-D4 groups, and the expression levels of lipid catabolism genes (cpt-1 and lpl) showed an upward trend. Moreover, the D2 group exhibited the lowest intestinal wall thickness, the mRNA levels of intestine anti-inflammatory cytokines (il-10) were up-regulated in the D2-D4 groups, and the highest mRNA levels of pro-inflammatory cytokines (il-8) were detected in the D2 group. In conclusion, the EFA deficiency leads to a decline in the growth and muscle quality of T. ovatus fed low marine diets, which cannot be mitigated by the addition of medium-short chain fatty acids. The results indicated that MCFA and SCFA cannot spare the EFA of low marine diets in T. ovatus. •Low marine diets with EFA deficiency against the growth and muscle quality of T. ovatus.•Supplementation with SCFA and MCFA cannot compensate the loss of dietary EFA deficiency.•With supplementation of SCFA and MCFA in the EFA deficiency diets impaired the hepatic lipid metabolism and health.•Adding of MCFA to low marine diets has some modification in the intestinal inflammation and health in T. ovatus.